Implementasi Akad Murabahah dan Akad Mudharabah Terhadap Profitabilitas (Studi Komparasi pada Bank Mega Syariah Surabaya dan Bank KB Bukopin Syariah Surabaya) - Wulansari, Andini; Efendi, Mansur; Faujiah, Siti Anisa Nur (PT. Kreasi Karya Majakata, 2025)
The purpose of the study was to see how effective the implementation of the two contracts is, namely in the process of implementation, identifying obstacles, and evaluating the obstacles and the profitability of the two contracts at Bank Mega Syariah Surabaya and Bank KB Bukopin Syariah Surabaya. The research method used is a descriptive qualitative method with Miles and Huberman analysis techniques, collecting data through in-depth interviews. Respondents are bank employees who are responsible for murabahah and mudharabah activities, namely the financing and marketing departments. The results of the study indicate that the effectiveness of the implementation of murabahah and mudharabah contracts in both banks is more effective in murabahah contracts compared to mudharabah contracts. This study contributes to the practice of murabahah and mudharabah contracts in the banking sector, while also offering recommendations for banks to increase the effectiveness of the implementation of mudharabah and murabahah contracts. In addition, this study is expected to provide customers with a better understanding of sharia principles in financial transactions